2020
DOI: 10.1002/pbc.28644
|View full text |Cite
|
Sign up to set email alerts
|

Psychological adjustment outcomes among pediatric brain tumor survivors: A meta‐analysis

Abstract: Background Pediatric brain tumor survivors (PBTS) are at significant risk for psychological adjustment difficulties, including greater depressive and anxious symptomology. Systematic reviews have identified this heightened risk among youth with medical conditions, but these reviews have not been specific to PBTS. Therefore, the current study aimed to directly examine the psychological adjustment of PBTS as compared to healthy peers. Procedure A systematic review and meta‐analysis was conducted using PubMed, Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 57 publications
(144 reference statements)
0
23
0
Order By: Relevance
“…8 Some studies have identified female sex and younger age at diagnosis as risk factors, but results have been mixed. [14][15][16] Protective factors include family social support, friend and peer connectedness, 17,18 survivor self-esteem, 13 and higher SES. 13,19 Survivors' physical health status and personal relationships, both of which have been disrupted due to the pandemic, have a particularly significant impact on quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…8 Some studies have identified female sex and younger age at diagnosis as risk factors, but results have been mixed. [14][15][16] Protective factors include family social support, friend and peer connectedness, 17,18 survivor self-esteem, 13 and higher SES. 13,19 Survivors' physical health status and personal relationships, both of which have been disrupted due to the pandemic, have a particularly significant impact on quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to neurocognitive late effects, PBTS are also at significant risk for poor psychological adjustment and quality of life 13,14 . The literature indicates that PBTS are at greater risk for internalizing difficulties, as compared to healthy peers and survivors of other cancers, with particularly strong meta‐analytic evidence for differences in depressive symptoms between PBTS and healthy comparisons 5,13,15,16 . These psychological problems appear to last well into adulthood, impacting the quality of life of long‐term survivors 4,5,10 .…”
Section: Introductionmentioning
confidence: 99%
“…These psychological problems appear to last well into adulthood, impacting the quality of life of long‐term survivors 4,5,10 . However, reports vary widely across the literature, suggesting that specific psychological sequelae may be dependent on factors such as age, symptoms assessed, and informant 2,13,14 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations